Aspects of Democratic Constitutionalism In The Appointment of Acting Regional Heads - Athari Farhani (UIN JAKARTA, 2022)
The upcoming General Elections and Regional Head Elections, which will be held in 2024, will reap probelmatics. One of them is about the appointment of acting regional heads which is considered contrary to democratic aspects, because there is no community involvement or inaccessibility to the mechanism for appointing acting regional heads. On the one hand, the Government does not heed the Decision of the Constitutional Court to issue implementing regulations as a follow-up to Article 201 of Law Number 10 of 2016 concerning Regional Elections. In fact, it is clear that the Constitutional Court is the guardion of constitution as well as the guardion of democracy. This is what makes the author want to do more research to answer the above problems. To answer this, the author uses a normative research method, namely by researching library materials or secondary data as basic materials for research. The approach used is a conceptual and statute approach.